2018
DOI: 10.12659/msm.907816
|View full text |Cite|
|
Sign up to set email alerts
|

miR-26a-5p Regulates Synovial Fibroblast Invasion in Patients with Rheumatoid Arthritis by Targeting Smad 1

Abstract: BackgroundWe studied the expression and effect of miR-26a-5p in synovial fibroblast in patients with rheumatoid arthritis (RA).Material/MethodsThe synovial tissues of 55 RA patients with total knee arthroplasty performed from January 2016 to December 2016 were collected as the RA group, and 62 patients without RA history amputation or total knee arthroplasty served as the control group. The expressions of miR-26a-5p and Smad 1 mRNA in synovial fibroblast in patients with RA were detected by qPCR; The expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…MiRNAs are attached to non-coding RNA and responsible to cellular and physiological processes by targeting protein-coding genes at post-transcriptional levels [18, 19]. MiR-26a-5p, locating on the human chromosome 3p22 [20], was the targeted downstream gene which predicted by target scan and functions in the development, differentiation, and cycle regulation for many cancers. For example, Xu et al demonstrated that miR-26a-5p potentiated lung cancer cell metastasis via JAK2/STAT3 pathway by targeting ITGb8 [19].…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs are attached to non-coding RNA and responsible to cellular and physiological processes by targeting protein-coding genes at post-transcriptional levels [18, 19]. MiR-26a-5p, locating on the human chromosome 3p22 [20], was the targeted downstream gene which predicted by target scan and functions in the development, differentiation, and cycle regulation for many cancers. For example, Xu et al demonstrated that miR-26a-5p potentiated lung cancer cell metastasis via JAK2/STAT3 pathway by targeting ITGb8 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Synovial tissue is an important part of the knee joint, which mostly includes synovial macrophages and fibroblast-like synoviocytes (FLS) (95); synoviocyte proliferation, invasion, and migration are essential for the RA pathology (96). Among synovial and FLS miRNAs, miR-21 (39), miR-26a-5p (41), miR-126 (50), miR-135a (51), miR-138 (54), miR-143 (56), miR-145 (56), miR-155 (58), and miR-421 (63) are overexpressed, whereas miR-19a (37), miR-20a (38), miR-22 (40), miR-27a (42), miR-29a (44), miR-34a (45), miR-137 (53), miR-140-3p (55), miR−152 (57), and miR-495 (68) are downregulated. The disturbed miRNAs enhance the expression level of proinflammatory cytokine (IL-6, IL-8, TNF-a, and IL-1b) and enzymes that erode the bone matrix (MMP-1 and MMP-3) by affecting Wnt (97,98), NF-kB (81,99), JAK/STAT (48,100), and TLR (101,102) pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Pannus formation is an important characteristic of RA, which is characterized by angiogenic factor-mediated angiogenesis and abnormal hyperplasia of the synovium (23). The pannus, which is composed mostly of FLS, is formed alongside a marked infiltration of lymphocytes and macrophages (24).…”
Section: Discussionmentioning
confidence: 99%